Intracellular Delivery II Fundamentals and Applications - Prokop, Aleš.; Prokop, Aleš.; Iwasaki, Yasuhiko.; Iwasaki, Yasuhiko.; Harada, Atsushi.; Harada, Atsushi. (Fundamental Biomedical Technologies, 2014)
This volume is a continuation of Volume 1 following the previously published Editorial. More emphasis is given to novel nanocarrier designs, their characterization and function, and applications for drug discovery and treatment. A number of chapters will deal with nanofibers as a new major application within the biomedical field with a very high success rate particularly in wound healing and diabetic foot and spine injuries. A major new subdivision will deal with mathematical methods for the assembly of nanocarriers  both for simulation and function.